Frontispiece: Lead(II) Formate in Rembrandt's Night Watch: Detection and Distribution from the Macro‐ to the Micro‐scale - Gonzalez, Victor; Fazlic, Ida; Cotte, Marine; Vanmeert, Frederik; Gestels, Arthur; De Meyer, Steven; Broers, Fréderique; Hermans, Joen; Loon, Annelies; Janssens, Koen; Noble, Petria; Keune, Katrien (Angewandte Chemie International Edition, 2023)
Heritage Science. In their Research Article (e202216478), Victor Gonzalez et al. report the detection and distribution of lead(II) formate in Rembrandt's Night Watch from the macro‐ to the microscale.